Morphological differences according to uterine tissue remodeling during estrus between sika deer and water deer - Oh, Min-Gee; Park, Yong-Su; Kim, Sang-Hwan (Journal of animal reproduction & biotechnology (Online), 2023)
Background: Water deer and sika deer, which breed in the wild environment, are known to have similar reproductive physiology mechanisms. Therefore, this study aimed to analyze the differences in uterine development between water deer and sika deer during estrus. Methods: MMPs and uterine development-related factors were analyzed and morphological differences were compared in the uterus of sika deer captured near Russia near Korea and water deer captured in the wild in Korea. Results: In terms of morphological differences in the uterus, the glands that form villus within the endometrium of the water deer were newly developed, and the formation of small glands was high, but the villus and glands of the sika deer were expanded, and the stroma zone in the myometrium was higher than that of the water deer. Development has increased. Additionally, the expression of PAPP-A and VEGF factors was increased in the endometrium of water deer than in sika deer, but the actions of MMPs were increased in sika deer. Conclusions: As a result of this study, there is a significant difference in the development of glands in the endometrium of water deer and sika deer during estrus, and it is believed that there is a significant difference in the development of the uterus due to the physiological effects of estrus between water deer and sika deer. Additionally, it is believed that there will be differences in the timing at which pregnancy can be decided.